P81 Audit of HIV testing in a lymphoma clinic. (18th May 2015) - LeVoir, Harriet; Wexler, Sarah; Horn, Kate
Abstract : Background/introduction: Non-hodgkins lymphoma (NHL) is the second most common malignancy in those with HIV, and AIDS related lymphomas (ARL) have increased as a percentage of first AIDS defining illness (ADI). Hodgkins lymphoma (HL) is a non AIDS defining malignancy but has 10 to 20 times higher incidence in those who are HIV positive. To assist in reducing late diagnosis of HIV, BHIVA guidelines in 2014 highlighted diseases where an HIV test should be offered including NHL and HL. Aim(s)/objectives: To establish whether patients newly diagnosed with NHL or HL in a large district general hospital lymphoma clinic were being tested for HIV in accordance with national and local guidelines. Methods: Patients newly diagnosed with NHL or HL from January 2013–January 2015 were identified via positive histology results recorded by the laboratory. Identification of HIV testing was via electronic blood results records. Results: Discussion/conclusion: Local haematology guidelines from 2014 indicate HIV and HCV/HBV testing for patients prior to Rituximab chemotherapy for lymphoma. The results indicate that since implementing guidelines, more HIV testing occurred, but without an increasing identification of undiagnosed HIV. A 2003 study investigating HIV positivity in newly diagnosed NHL identified HIV positive patients had more aggressive lymphoma histology and increased B symptoms. Continued testing for HIV in lymphoma, especially if presenting with B symptoms, is recommended.